PENGARUH EFEKTIFITAS, EFISIENSI DAN KESERASIAN TERHADAP KEMANDIRIAN KEUANGAN DAERAH - . Marnas; Afrizal; Yuliusman (Magister Ilmu Akuntansi Universitas Jambi, 2016)
The purpose of this study is to determine the effect of effectiveness, efficiency and harmony, the regional financial independence either partially or simultaneously (Actual case study on district budget / Environment City in Jambi Province) 2008 -2012. Data used in this study is secondary data. Data in the form of financial ratios in assessing performance accountability district budget and municipal in Jambi Province on the district budget realization report and municipal in Jambi Province in 2008 and 2012. Research is explanatory research is clear that analysis financial ratios in the budget in the form of effectiveness, efficiency, harmony, growth, and the proportion of income and expenditure in the district budget and municipal in Jambi Province has an influence on independence. The district budget and municipal in Jambi Province in demonstrating the ability of local governments to finance their own activities of government, development, and service to the community. The instruments used in this study statistics with multiple linear regression analysis to determine the level of the relationship and knowledge of public accounting as a tool The main analysis. Statistical Analysis Based on the analysis it is known that the area ratio effectiveness significant negative effect on self-sufficiency ratio. Therefore, when the effectiveness of PAD to the target area increases, this effect of reducing the independence of the district budget as Jambi City, the number PAD District Municipality is a very small amount and is unable to independently meet the needs of a budgeting cost, regional financial efficiency ratios significant positive effect on the independence of the public service. So if the financial efficiency of the region tends to be better, it is an against budget independence. Because the average - average development cost is top shopping district budget as Jambi City, more than the total earnings (deficit), Harmony ratio of public expenditure to the independence of development or PAD District or City to significant negative effect on public services. So if your chance in shopping activities tend to be better, it does not affect the independence of local revenues. Due average - above average shopping district budget financing municipal in Jambi province cannot afford financed by a small PAD. Simultaneously, it can be concluded that the variable effectiveness, efficiency and harmony by together - equally significant effect on Financial independence Jambi City District. So if effectiveness, efficiency and harmony together increases, the independence of the Financial District City in the province of Jambi. Would be also increase.